THE INFLUENCE OF CINDER AS REPLACEMENT OF ROUGH AGGREGATE OF VARIATIONS BASED ON PERCENTAGE OF STRENGTH AND WEIGHT PULL TYPE CONCRETE MIX DESIGN METHOD - Susilaningsih, Arin; Saputro, Ida Nugroho; Sutrisno, Sutrisno (Pendidikan Teknik Bangunan, 2014)
ABSTRACT The purpose of this study is to, (1) determine the positive influence of slag as coarse aggregate for concrete tensile strength, (2) determine the effect of the possitive slag concrete density, (3) investigating optimal persentage of slag as a substitute for coarse aggregate that produces a maximum tensile strength of concrete, (4) investigate the optimal percentage of slag as a substitute for coarse aggregate that produces normal density concrete. This research is quantitative. The variables that influence directly in this study were (1) the dependent variable: tensile strength and density of concrete, (2) independent variables: the percentage of the variation slag replacement 0%, 20%, 40%, 60%, 80%, 100% . Based on the results of this study concluded that (1) the use of slag as a coarse aggregate replacement level being influenced by the tensile strength of concrete. The resulting negative influence, because the tensile strength of concrete decreased with increasing percentage of slag. (2) The use of slag as a coarse aggregate replacement very strong influence on the density of the concrete. Concrete density increased with increasing percentage of slag. (3) are obtained optimal percentage of slag as a substitute for coarse aggregate in the concrete tensile strength, because the tensile strength of concrete decreased with increasing percentage of slag replacement. (4) Percentage of optimum still produce normal weight concrete types is at 80% which is 2491 kg/m3. Conclusion from this research is influenced by the level of slag are the tensile strength of concrete and slag very strong influence on the density of the concrete.Keywords: concrete, slag, tensile strength, density